2012
DOI: 10.1111/j.1465-3435.2011.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Doctorates and Careers: the Spanish case1

Abstract: This article analyses the determining factors weighted by doctoral graduates when choosing their professional careers. In Spain, the analysis of such a group has been traditionally excluded from the empiric studies. On the one hand, the lack of databases made it difficult to see their professional situation, and on the other, a university career was understood as this group's innate purpose. The growing demand for qualified professionals in general and for those with a scientific training in particular has pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Its main aim was to measure employment, international mobility, gross annual income, job satisfaction and research productivity (via publications and patents) of all types of PhD degree holders (ISCED‐97 level 6). Some of the main features of the survey and the sample may also be found in Canal Domínguez & Muñiz Pérez (). Since the ERRHCT2006 was designed according to European regulations (Commission Regulations (EC) No 1450/2004 and No 753/2004, based on Decision No 1608/2003/EC of the European Parliament and of the Council concerning the production and development of Community statistics on science and technology), the questionnaire enhances comparability with countries that take part in the Careers of Doctorate Holders (CDH) project initiated by EUROSTAT, the OECD and UNESCO (see Schwabe () for an illustration of the key findings stemming from the Austrian CDH data collection).…”
Section: Methodsmentioning
confidence: 99%
“…Its main aim was to measure employment, international mobility, gross annual income, job satisfaction and research productivity (via publications and patents) of all types of PhD degree holders (ISCED‐97 level 6). Some of the main features of the survey and the sample may also be found in Canal Domínguez & Muñiz Pérez (). Since the ERRHCT2006 was designed according to European regulations (Commission Regulations (EC) No 1450/2004 and No 753/2004, based on Decision No 1608/2003/EC of the European Parliament and of the Council concerning the production and development of Community statistics on science and technology), the questionnaire enhances comparability with countries that take part in the Careers of Doctorate Holders (CDH) project initiated by EUROSTAT, the OECD and UNESCO (see Schwabe () for an illustration of the key findings stemming from the Austrian CDH data collection).…”
Section: Methodsmentioning
confidence: 99%
“…From 2005-2009, only 16,000 new professorships were created in the U.S., though more than 100,000 doctoral degrees were granted ("The disposable academic," 2010). Indeed, in one of the few post-graduation studies of professional doctoral holders, Spain's labor market was shown to not yet value postdoctoral education: doctors of humanities and social sciences (including economics and business administration) reported experiencing low job satisfaction and low expected wages ( Canal Domínguez & Muñiz Pérez, 2012).…”
Section: Graduate Outcomesmentioning
confidence: 99%
“…They also find that the negative impact of mismatch on job satisfaction is the same regardless of whether PhD holders are employed in academic or nonacademic jobs. Schwabe (2011) andCanal-Domínguez andMuñiz-Pérez (2012) analysed, respectively, Austrian and Spanish data of the 2006 CDH survey. They examined unconditional differences in job domains satisfaction among doctors in the Austrian and in the Spanish labour markets, obtaining that those who work outside the academy tend to be more satisfied with earnings -but less satisfied with non-monetary aspects of the job -than their academic counterparts.…”
Section: ) Related Researchmentioning
confidence: 99%
“…On the other hand, the progressive contraction of academic hiring in universities (and research institutes) due to public spending cuts and the overall structural changes of the Spanish university system are likely to create queues for academic jobs among new PhD graduates and to increase the likelihood of being employed outside the traditional academic sector (Canal-Domínguez & Muñiz-Pérez, 2012). This overall situation opens the door to a substantial incidence of 'underemployment' among PhD holders in Spain, where the number of PhD holders is increasing substantially and exceeds the number of jobs that are suitable for them.…”
mentioning
confidence: 99%